The supernatural ways of royalty - Vallotton, Kris.; Johnson, Bill. (Shippensburg, PA : Destiny Image Pub., 2006)
Reveals your true identity as a child of the King of Kings, royal heir to the eternal kingdom of God. The authors denounce the "pauper mentality" many Christians have and present your royal inheritance through Christ's ultimate act of redemption.
Keywords: Self-actualization (Psychology) -- Religious aspects -- Christianity; Spiritual formation